As pessoas com deficiência no mercado de trabalho: expressão das desigualdades sociais - Severino, Maria do Perpétuo Socorro Rocha Sousa (2007)
This work was developed in the extent of the Post Graduation Program in Social Service of the Federal University of Rio Grande do Norte. It talks about the process of inclusion of the disabled people in the Job market in Mossoró-RN, bringing for the academic debate relevant thematic for the Brazilian society, for the profession of Social Service and similar areas and for the people with deficiency. It has the objective to apprehend the determiners that make possible the process of the disabled people's inclusion in the Job market in Mossoró, having as parameter the National Politics for the Integration of People Bearers of Deficiency. The critical theoretical perspective is backed in Marx's ideas for the understanding concerning the work, as well as in Pochamann, concerning the job market, regarding the exclusion/inclusion category is based in Martins, Yasbek and Sposati and on deficiency in the National Politics for the Integration of the Disabled People. The research is of qualitative nature and it took as subjects 26 (twenty-six) people, being 09 (nine) people with deficiency, inserted in the formal job and regulated market, and 17 (seventeen) managers of private companies and public institutions of the city of Mossoró-RN. For the collection of data we used techniques of nonsystemic observation, semi-structured interview and documental analysis. The results of the research mark that any modality of the human workforce used in the current context, they are functional to the capitalism and they move forward towards exploration, alienation and subordination of the work to the capital; the National Politics for the Integration of the People with Deficiency expresses and reproduces the contradictory dynamics of the class society, it reflects the neo liberal shades through the selectivity and of the articulation among the federated beings and organizations of the civil society for its operational system; there is a misproportion between the percentages of the quotas and the amount of people with deficiency inserted in the job market, just corresponding to a tiny numeric magnitude; the developed activities are of low social status and it is expressive the amount of workers that receives between one and two minimum wages. These data drive us to infer that the mentioned politics make possible, partly, the inclusion of the disabled people in the job market, though, such inclusion is executed in the selective or focused dimensions, marginal, precarious and unstable